Wetting by liquid sodium and fracture path analysis of sodium induced embrittlement of 304L stainless steel. Issue 2 (27th November 2017) - Barkia, Bassem; Auger, Thierry; Courouau, Jean-Louis; Bourgon, Julie
Abstract: Abstract : The wettability of the 304L steel is an important parameter in Liquid Metal Embrittlement studies. Empirically, it is found to be greatly enhanced by pre-exposure to oxygenated liquid sodium. The corrosion interface formed during exposure to sodium has been analyzed at the nanoscale by transmission electron microscopy using the focused ion beam sampling. A thin layer of sodium chromite (Na x CrO2 with x ≤ 1) is detected at the interface validating wetting on an oxide mechanism for the enhanced wetting after pre-exposure. Fracture micromechanisms and the crack path of liquid sodium-embrittled austenitic steel 304L at 573 K have been investigated down to the nanoscale. High-resolution orientation mapping analyses immediately below the fracture surface show that abundant martensitic transformations (γ → α) and twinning occur during deformation of austenite. The preferential crack path is intergranular along the newly formed γ/γ interfaces. It is concluded that these transformations play a major role in the fracture process.